1987
DOI: 10.1136/jcp.40.10.1178
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of culture media for detecting methicillin resistance in Staphylococcus aureus and coagulase negative staphylococci.

Abstract: SUMMARY The detection of methicillin resistance was examined in 51 strains of Staphylococcus aureus and 135 strains of coagulase negative staphylococci using Isosensitest, Diagnostic Sensitivity Test (DST), Mueller-Hinton (MH), Columbia, and Sensitest agars. MH agar with 5% added sodium chloride incubated at 35°C was the most effective in detecting resistance in S aureus, and Columbia agar with 5% added sodium chloride incubated at 35°C was most effective for coagulase negative staphylococci. For clinical purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…All 31 strains had no zones of inhibition around methicillin (10 µg) and cephalexin (30 µg) disks, and 26 demonstrated reduced zones of inhibition for cephalothin (30 µg) and cephaloridine (30 µg) on trypticase soy agar containing 5% sodium chloride. When DD was performed on Mueller-Hinton agar, the same 26 strains demonstrated zones of 25–30 mm, which would have been interpreted as susceptible using former CLSI breakpoints, around the cephalothin and cephaloridine disks, confirming the ability of sodium chloride to improve the detection of β-lactam resistance [72] as well as the heterogeneous expression of resistance in these strains. MRS was recovered from blood culture after initiation of cephalosporin therapy in 21 of these patients, 20 of whom remained culture positive after day 3 of cephalosporin therapy.…”
Section: Clinical Data Supporting Clsi Recommendationsmentioning
confidence: 84%
“…All 31 strains had no zones of inhibition around methicillin (10 µg) and cephalexin (30 µg) disks, and 26 demonstrated reduced zones of inhibition for cephalothin (30 µg) and cephaloridine (30 µg) on trypticase soy agar containing 5% sodium chloride. When DD was performed on Mueller-Hinton agar, the same 26 strains demonstrated zones of 25–30 mm, which would have been interpreted as susceptible using former CLSI breakpoints, around the cephalothin and cephaloridine disks, confirming the ability of sodium chloride to improve the detection of β-lactam resistance [72] as well as the heterogeneous expression of resistance in these strains. MRS was recovered from blood culture after initiation of cephalosporin therapy in 21 of these patients, 20 of whom remained culture positive after day 3 of cephalosporin therapy.…”
Section: Clinical Data Supporting Clsi Recommendationsmentioning
confidence: 84%
“…Such a low-level resistance has not yet been described in S. epidermidis. Isolates with this mechanism of resistance would not be demonstrated using a mecA-specific PCR and probably not using the broth tube breakpoint test where the breakpoint is relatively high, 16 mg/l methicillin. However, they may have zones smaller than those of the susceptible isolates in a disc diffusion test.…”
Section: Discussionmentioning
confidence: 99%
“…Using another method, agar dilution, other workers have shown that the choice of medium is important when testing S. uureus (11) and coagulase-negative staphylococci ( 1 6). In these tests an increased concentration of NaCl in the medium enhances growth of the resistant subpopulations, but 48 h incubation is necessary for detection of all resistant strains of S. epidermidis ( 10,16). In the disc diffusion test the influence of the medium is on the size of the inhibition zone and breakpoints can be chosen where resistant and susceptible strains are best separated.…”
Section: Discussionmentioning
confidence: 99%
“…This has increased interest in optimal methods for MRSA recognition. Several papers on the subject have been published recently (5)(6)(7)(8)(9)(10). These studies make clear that there are different views on the criterion to use in defining methicillin resistance, i.e.…”
mentioning
confidence: 98%